2012
DOI: 10.1186/1297-9716-43-44
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Salmonella Gallinarum ghost as a novel inactivated vaccine candidate and its protective efficacy against fowl typhoid in chickens

Abstract: In order to develop a novel, safe and immunogenic fowl typhoid (FT) vaccine candidate, a Salmonella Gallinarum ghost with controlled expression of the bacteriophage PhiX174 lysis gene E was constructed using pMMP99 plasmid in this study. The formation of the Salmonella Gallinarum ghost with tunnel formation and loss of cytoplasmic contents was observed by scanning electron microscopy and transmission electron microscopy. No viable cells were detectable 24 h after the induction of gene E expression by an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 43 publications
1
48
0
2
Order By: Relevance
“…It should be noted that the new strategy for NaOH-induced BGs was fast [13]. Moreover, other researchers [17] have shown the lysis efficiency of genetically inactivated BGs after lysis was 99.9%.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noted that the new strategy for NaOH-induced BGs was fast [13]. Moreover, other researchers [17] have shown the lysis efficiency of genetically inactivated BGs after lysis was 99.9%.…”
Section: Resultsmentioning
confidence: 97%
“…The resultant BGs share their functional and antigenic determinants of the envelope and represent an excellent vaccine candidate [12]. BGs from pathogenic bacteria were reported to be controlled and can protect against infectious diseases [13]. The mucosal immunizations with Escherichia coli ghosts were reported to induce protective immunity in an SPF chicken model [14].…”
Section: Introductionmentioning
confidence: 99%
“…As bacterial ghosts retain all of the surface immunogenic determinants of their living counterparts, they are capable of stimulating strong immune responses, and their vaccine potential has been demonstrated experimentally for the prevention of pathogenic Gram-negative bacterial infections of veterinary importance Marchart et al, 2003;Chaudhari et al, 2012;Jawale et al, 2012;Hu et al, 2013). Here, we used Salmonella Typhimurium ghosts carrying LTB for vaccination experiments in the chicken model.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination trials in the laboratory or food-producing animals have demonstrated the ability of bacterial ghost vaccines to stimulate strong induction of immune responses accompanied by significant protection against virulent challenge (Wang & Lu, 2009;Chaudhari et al, 2012;Jawale et al, 2012;Hu et al, 2013). In our experiments, we employed only a fixed time window for challenge and reisolation of the bacteria, and a high dose of virulent challenge strain was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation